Bobbio and the democratic dualisms: from civil society’s demands to the public privatization - Cadermartori, Daniela Mesquita Lutchuk de (2017)
This essay seeks to realize in Bobbio’s democratic theory, dualisms, paradoxes and what he called unfulfilled promises of democracy. Among the dualisms, the first is to expose the theme through the conflict between ideals and “rude matter”. Is also analyzes the increasing demands of contemporary society, the relations between democracy, bureaucracy and technocracy, and what the author considered as mistaken perceptions of the problems that involves the privatizations of the public ant the survival of the oligarchies. The analyses is based on a multifaced perspective, so as to enable a provisional synthesis of studies and research, establishing a dialogue about common issues between the current problems of democracy and the contribution of Bobbian thought.